2009
DOI: 10.1158/1055-9965.epi-08-0462
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 2 and Head and Neck Cancer: A Meta-analysis Implementing a Mendelian Randomization Approach

Abstract: Alcohol drinking at high doses is a risk factor for head and neck cancer, and exposure to acetaldehyde, the principle metabolite of alcohol, is supposed to account for the increased risk. Individuals homozygous for the *2 variant allele of aldehyde dehydrogenase 2 (ALDH2) are unable to metabolize acetaldehyde, which prevents them from alcohol drinking, whereas *1*2 have 6-fold higher blood acetaldehyde concentration postalcohol consumption with respect to *1*1. According to the concept of Mendelian randomizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 27 publications
11
93
0
Order By: Relevance
“…The reduction in risk is close to that predicted from the size of effect of genotype on alcohol consumption and the dose-response association of alcohol and oesophageal cancer risk [80]. A similar picture is seen when head and neck cancer is the outcome [81].…”
Section: Gene-by-environment Interactions Interpreted Within a Mendelsupporting
confidence: 72%
See 1 more Smart Citation
“…The reduction in risk is close to that predicted from the size of effect of genotype on alcohol consumption and the dose-response association of alcohol and oesophageal cancer risk [80]. A similar picture is seen when head and neck cancer is the outcome [81].…”
Section: Gene-by-environment Interactions Interpreted Within a Mendelsupporting
confidence: 72%
“…8). A similar analysis has been performed for head and neck cancer and again demonstrates no association of genotype and cancer risk in never drinkers and a graded association according to level of alcohol intake among alcohol drinkers [81].…”
Section: Gene-by-environment Interactions Interpreted Within a Mendelsupporting
confidence: 55%
“…The presence of carbonyl groups in overheated oil may constitute a serious risk to the human body. It was reported that aldehydes are potentially toxic substances with possibility to induce different cancers when consumed [26][27][28] . Furthermore, it is known that asparagine and reducing sugars are relatively in high amount in potatoes, and that both compounds are the main precursors of acrylamide, which is formed during frying, baking, grilling or toasting carbohydrates rich foods 19,29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Study participants were recruited among patients admitted to the teaching hospital "Agostino 15.9% oral cavity, and 21.3% pharyngeal. Controls were selected from among cancer-free patients admitted to the same hospital during the same time period with a broad range of diagnoses.…”
Section: Study Population and Genotypingmentioning
confidence: 99%
“…Generally speaking, studying the association between sequence variants of genes (e.g., apoE) known to be related to an intermediate phenotype (e.g., serum cholesterol level) and a disease has the advantage of being less prone to the confounding effect of lifestyle factors or disease stage that might affect the association between the intermediate phenotype and the disease itself. This approach has been called "Mendelian randomization" (14,15), and it has been recently adopted to evaluate the association between cholesterol levels and cancer risk by using the apoE genotype as a surrogate for cholesterol levels. Results, however, are largely conflicting (7,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%